Trials & Tribulations of Liver Transplantation‐ are trials now prohibitive without surrogate endpoints?. Issue 5 (30th April 2021) - Richards, James; Gimson, Alex; Joh, Yexin; Watson, Christopher J.E.; Neuberger, James
Abstract : During the past 5 decades, liver transplantation has moved from its pioneering days where success was measured in days to a point where it is viewed as a routine part of medical care. Despite this progress, there are still significant unmet needs and outstanding questions that need addressing in clinical trials to improve outcomes for patients. The traditional endpoint for trials in liver transplantation has been 1‐year patient survival, but with rates now approaching 95%, this endpoint now poses a number of significant financial and logistical barriers to conducting trials because of the large numbers of participants required to demonstrate only an incremental improvement. Here, we suggest the following solutions to this challenge: adoption of validated surrogate endpoints; bigger and better collaborative multiarm, multiphase studies; recognition by funders and institutions that work on larger collaborative research projects is potentially more important than smaller, self‐led bodies of work; ringfenced areas of research within trial frameworks where individuals can take a lead; and fair funding structures using both industry and public sector money across national and international borders.